Genetic Variability of Antioxidative Mechanisms and Cardiotoxicity after Adjuvant Radiotherapy in HER2-Positive Breast Cancer Patients - Marinko, Tanja; Stojanov Konda, Jakob Timotej; Dolžan, Vita; Goričar, Katja (Disease Markers, 2020)
Background. Breast cancer treatment is associated with the occurrence of various cardiac adverse events. One of the mechanisms associated with cardiotoxicity is oxidative stress, against which cells are protected by antioxidative enzymes. Genetic variability of antioxidative enzymes can affect enzyme activity or expression, which modifies the ability of cells to defend themselves against oxidative stress and could consequently contribute to the occurrence of treatment-related cardiotoxicity. Our aim was to evaluate the association of common polymorphisms in antioxidative genes with cardiotoxicity after adjuvant radiotherapy (RT) in HER2-positive breast cancer patients. Methods. Our retrospective study included 101 HER2-positive early breast cancer patients who received trastuzumab and adjuvant RT. We isolated DNA from buccal swabs and used competitive allele-specific PCR for genotyping of PON1 rs854560 and rs662, GSTP1 rs1138272 and rs1695, SOD2 rs4880, CAT rs1001179, and HIF1 rs1154965 polymorphisms. N-terminal pro B-type natriuretic peptide (NT-proBNP), left ventricular ejection fraction, and NYHA class were used as markers of cardiotoxicity. We used logistic regression to evaluate the association of genetic factors with markers of cardiotoxicity. Results. Carriers of at least one polymorphic PON1 rs854560 allele were less likely to have increased NT-proBNP (OR=0.34; 95% CI = 0.15-0.79; P=0.012), even after adjustment for age (OR=0.35; 95% CI = 0.15-0.83; P=0.017). Carriers of at least one polymorphic PON1 rs662 allele were more likely to have increased NT-proBNP (OR=4.44; 95% CI = 1.85-10.66; P=0.001), even after adjustment for age (OR=5.41; 95% CI = 2.12-13.78; P<0.001). GSTP1 rs1695 was also associated with decreased NT-proBNP in the multivariable analysis (P=0.026), while CAT rs1001179 was associated with NYHA class in the univariable (P=0.012) and multivariable analysis (P=0.023). Conclusion. In our study, polymorphisms PON1 rs662 and rs854560, CAT rs1001179, and GSTP1 rs1695 were significantly associated with the occurrence of cardiac adverse events after adjuvant RT and could serve as biomarkers contributing to treatment personalization.